AB0132 Four cases in which the initial illness was typical of reiter`s syndrome and later became typical psoriatic arthritis. (1st June 2001) - Imre, K; Koo, E; Sesztak, M
Abstract : Background: It is generally accepted that in some patients reactive arthritis may progress further to ankylosing spondylitis. A generally accepted estimate is that 20 percent of patients with Reiter`s syndrome develop peripheral arthritis or axial disease. Objectives: The study group consisted of 500 unrelated consecutive patients with psoriatic arthritis at 15 year follow up at the PsA outpatient clinic. We found four cases in which the initial illness was typical of Reiter`s syndrome and later became typical psoriatic arthritis. Methods: Results: One patient had persistent joint symptoms, two patients have at every 5 years recurrent bouts of arthritis and one patient suffered from severe, aggressive and unremitting disease. Over 1 to 5 years the skin lesions progressively assume the characteristics of psoriasis. The diagnosis of PsA was set up among 1–10 years. Conclusion: The possibility that psoriatic arthritis and Reiter`s syndrome may be similar or closely related is illustrated by our cases, too. Such cases have suggested a more than coincidental interrelationship between Reiter`s syndrome and psoriatic arthritis.